Proceso innovador y capacidad de creación de espacio de los Servicios avanzados (SA) en Andalucía - Jordà Borrell, Rosa (Geographicalia, 2016)
This paper studies the features of the environment of production of the Advanced Services (AS) firms in order to understand their technological level. We have also analyzed the environment of production in Andalusia. The investigation has looked for the technological and non-technological behaviour of these firms, organisation of production and the demand flows as regards buying and selling and co-operation relations. The results obtained indicate that the AS companies make a srnaller investment on K-D cormparing with the investment found in industries, being this in a 8 to 1 proportion. On the other hand, the main investment for the AS companies lies in human resources. Quality control and consulting firrns show the highest concentration of services hired (31.5% and 31.3% respectively) in contrast with the Public Research Institutions (PRIs) which provide the largest number of services hired on R-D to the different economical sectors. In most cases, the destination of the services provided by these AS firms and co-operation is found in other companies established in Andalusia (63% and 76.6% respectively) but the density of relations is low and scarcely continuing. PRIs and quality control and consulting firms are the key elements for the structuration of innovation space in Andalusia.
Keywords: Andalusia; Advanced Services (AS); technological behaviour; organisation of production and the demand flows